2014
DOI: 10.1080/13548506.2014.987147
|View full text |Cite
|
Sign up to set email alerts
|

The influence of early sexual debut and pubertal timing on psychological distress among Taiwanese adolescents

Abstract: This study examined the relative influence of early sexual debut (ESD) and pubertal timing on psychological distress from adolescence to young adulthood in Taiwan, a non-Western society with a distinct cultural and family context. Data were from a cohort sample of 15-year-olds (N = 2595) first interviewed in 2000, with four follow-ups during a 7-year period. Psychological distress was assessed by a reduced form of the Symptom Checklist-90 Revised. ESD was defined by first intercourse at age 15 or younger. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
(22 reference statements)
1
10
0
3
Order By: Relevance
“…Two indirect findings may address this concern. First, literature has shown that early pubertal timing is related to delinquency and depression [84][85], and two studies that used the same dataset as this study have demonstrated this relationship [80,86]. Second, the distribution of age of menarche from a national representative sample of Taiwanese adolescents was very similar to the present sample (national representative sample: 82.8% before or at 7 th grade; current study: 88% before or at 7 th grade) [87].…”
Section: Pubertal Timing (Wave 1)supporting
confidence: 60%
See 1 more Smart Citation
“…Two indirect findings may address this concern. First, literature has shown that early pubertal timing is related to delinquency and depression [84][85], and two studies that used the same dataset as this study have demonstrated this relationship [80,86]. Second, the distribution of age of menarche from a national representative sample of Taiwanese adolescents was very similar to the present sample (national representative sample: 82.8% before or at 7 th grade; current study: 88% before or at 7 th grade) [87].…”
Section: Pubertal Timing (Wave 1)supporting
confidence: 60%
“…The responses and grouping scheme were identical to those for girls. This grouping method has been used in previous studies [80][81] and the reliability and validity of the PDS have been confirmed [82]. The PDS has been shown to provide a suitable measure of puberty and to capture the subjective and social aspects of pubertal development [83].…”
Section: Pubertal Timing (Wave 1)mentioning
confidence: 93%
“…The summed score across all items was standardized and it was gender and age specific. Those individuals who were one standard deviation above the mean were grouped into the “early maturation” group, while the others were grouped into the reference group ( Chiao and Ksobiech, 2015 , Sun et al, 2017 ). Lack of sleep was based on the individual's self-reported sleep hours and was dichotomized into a lack of sleep (daily sleep hours < 6 hours) and adequate sleep ( Lin & Yi, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Psychological well-being was measured by four self-reported indicators: depressive symptoms, self-esteem, suicidal thoughts, and alcohol use. Depressive symptoms were assessed using an 8-item version of the Symptom Checklist-90 Revised (SCL-90-R) scale [1719]. The SCL-90-R is an instrument with good construct validity and reliability when used with Taiwanese adolescents [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Depressive symptoms were assessed using an 8-item version of the Symptom Checklist-90 Revised (SCL-90-R) scale [1719]. The SCL-90-R is an instrument with good construct validity and reliability when used with Taiwanese adolescents [19,20]. Each five-point scale indicates the degree to which each symptom had been experienced within the past week.…”
Section: Methodsmentioning
confidence: 99%